AIR: Advances in Respiration – Music therapy in the treatment of chronic pulmonary disease. Issue 12 (December 2015) - Canga, Bernardo; Azoulay, Ronit; Raskin, Jonathan; Loewy, Joanne
Abstract: The aim of this randomized control study is to examine the effect of a multimodal psycho-music therapy intervention on respiratory symptoms, psychological well-being and quality of life of patients with Chronic Obstructive Pulmonary Disease and other lung diseases as adjunct to Pulmonary Rehabilitation with a design of music therapy plus PR compared to Pulmonary Rehabilitation alone. Music therapy group treatment including music visualization, wind playing and singing was provided weekly. This was compared with standard care treatment. Adults ages 48 to 88 (mean 70.1) with moderate to severe GOLD stage II-IV lung disease as well as other diseases processes that lead to chronic airflow limitations were included (n = 98). Participants in both conditions were followed from baseline enrollment to six weeks post control/treatment. Outcome measures included the Beck Depression Inventory Scale 2nd edition-Fast Screen (BDI-FS), Chronic Respiratory Questionnaire Self-Reported (CRQ-SR), and Dyspnea Visual Analog Scale (VAS). Results showed improvement in symptoms of depression (LS mean −0.2) in the music therapy group with statistical divergence between groups (p = 0.007). The CRQ-SR demonstrated improvement in dyspnea (p = 0.01 LS mean 0.5) and mastery (p = 0.06 LS mean 0.5) in the music therapy group and fatigue (p = 0.01 LS mean 0.3). VAS demonstrated highly significant effect in the music therapy group between weeks 5 and 6 (p < 0.001). The findings of this study suggest that music therapy combined with standard PR may prove to be an effective modality in the management of pulmonary disease.